Recent Progress in Understanding the Action of Natural Compounds at Novel Therapeutic Drug Targets for the Treatment of Liver Cancer - Zheng, Yannan; Zhang, Wenhui; Xu, Lin; Zhou, Hua; Yuan, Man; Xu, Hongxi (Frontiers in Oncology, 2022)
Liver cancer is the third most common cause of cancer-related death following lung and stomach cancers. As a highly lethal disease, liver cancer is frequently diagnosed in less developed countries. Natural compounds extracted from herbs, animals and natural materials have been adopted by traditional Chinese medicine (TCM) practices and reported to be effective in the development of new medications for the treatment of diseases. It is important to focus on the mechanisms of action of natural compounds against hepatocellular carcinoma (HCC), particularly in terms of cell cycle regulation, apoptosis induction, autophagy mediation and cell migration and invasion. In this review, we characterize novel representative natural compounds according to their pharmacologic effects from recently published literature. The aim of this review is to summarize and explore novel therapeutic drug targets of natural compounds, which could accelerate the discovery of new anticancer drugs.